Pengaruh simultan dan parsial supervisi kepala sekolah, disiplin kerja, dan lingkungan kerja terhadap kinerja guru SMK di Wonosobo - Fathurohman, Muhammad; Supriyoko, Supriyoko (Indonesian Journal of Educational Management and Leadership, 2024)
Purpose – The purpose of this study was to determine the effect of principal supervision, work discipline, and work environment on the performance of vocational high school teachers in the Wadaslintang sub-district of Wonosobo district both simultaneously and partially . Method − T This research uses a quantitative approach. The sample in this study was 88 teachers. Data collection using survey techniques, with a questionnaire as the research instrument. The analysis used is multiple linear regression analysis Findings − The results showed that: (1) There is a positive and significant effect of principal supervision, work discipline, and work environment together on the performance of vocational high school teachers in the Wadaslintang sub-district of Wonosobo Regency. (2) There is a positive and significant effect of principal supervision on the performance of vocational school teachers in the Wadaslintang sub-district of Wonosobo Regency. (3) There is a positive and significant effect of work discipline on teacher performance at SMKs in Wadaslintang Sub-district, Wonosobo Regency. (4) There is a positive and significant effect of the work environment on the performance of teachers at SMKs in Wadaslintang Sub-district, Wonosobo Regency.